Household food insecurity and obesity risk in preschool-aged children: A three-year prospective study. (August 2022) - Zhong, Danruo; Gunnar, Megan R.; Kelly, Aaron S.; French, Simone; Sherwood, Nancy E.; Berge, Jerica M.; Kunin-Batson, Alicia
Abstract: Background: Household food insecurity (FI) is a pressing social, economic and public health issue. However, little is known regarding the effect of FI exposure during the first few years of life, the most active postnatal time for neurobiological and physiological development, on patterns of weight gain during early childhood. It is also unknown whether dietary quality would serve as a pathway through which FI affects children's weight development. Method: This was a secondary data analysis from a three-year randomized clinical trial with five hundred and thirty-four parent/child dyads. Household FI in the past year was reported by parents at baseline when children were 2–4 years of age using the USDA Household Food Security Survey Module-Six Item Short Form. Children's dietary quality at baseline was measured by the US Department of Agriculture Healthy Eating Index (HEI). Child body mass index (BMI) was measured following standardized protocols at baseline and 12-, 24-, and 36-month follow-up. A latent growth curve model was used to examine 1) the association between baseline FI and sex-and-age-adjusted BMI z-scores in children and 2) the HEI pathway between the FI- BMI association. Results: FI early in life was associated with higher baseline BMI z-scores. Children who had higher BMI at baseline maintained their higher BMI status over the next three years. Children's dietary intake quality did not explain the association between baseline FI and BMI z-scores. Conclusion: Early exposure to FI was associated with higher BMI in children as early as two years of age, setting them up for an increased likelihood of persistently high BMI-for-age in later childhood. These data suggest that the first few years may be a critical time for developing obesity risk, calling for policy and practices designed for early intervention of food insecurity. Highlights: Food insecurity was associated with children's BMI as early as 2–4 years of age. Dietary intake did not explain the food insecurity-children's BMI association. Policy and practices should reduce food insecurity to prevent childhood obesity.